Prognostic Potential of Metabolic Activity on 18F-FDG Accumulation in Advanced NSCLC Receiving Combining Chemotherapy Plus PD-1 Blockade. Issue 8 (19th October 2022) - Hashimoto, Kosuke; Kaira, Kyoichi; Imai, Hisao; Mouri, Atsuto; Shiono, Ayako; Miura, Yu; Yamaguchi, Ou; Kobayashi, Kunihiko; Kagamu, Hiroshi; Kuji, Ichiei
Abstract : Combined chemotherapy plus programmed death-1 (PD-1) blockade is an established treatment against patients with advanced non–small cell lung cancer (NSCLC). However, a promising predictor besides programmed death ligand-1 expression remains uncertain. We examined the prognostic significance of baseline 18 F-FDG-positron emission tomography for predicting first-line combined chemotherapy plus PD-1 blockade in NSCLC patients. Forty-five patients with advanced NSCLC who received 18 F-FDG-positron emission tomography immediately before combined platinum-based chemotherapy with PD-1 blockade as first-line setting were eligible for this study, and assessment of maximum of standard uptake value (SUVmax ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) on 18 F-FDG uptake was performed. The objective response rate, median progression-free survival, and overall survival were 51.2%, 206 days, and 681 days, respectively. High SUVmax, TLG, and MTV significantly correlated with age and performance status (PS), C-reactive protein (CRP), and PS, CRP, albumin, and baseline tumor size, respectively. Univariate analysis identified albumin, TLG and MTV as significant predictors of progression-free survival, and CRP, albumin, TLG and MTV as significant factors for predicting overall survival. High TLG was confirmed as an independent factor associated with poor prognosis in multivariate analysis. In particular, TLG is identified as the most powerful predictor in patients with good PS, adenocarcinoma, programmed death ligand-1≥1%, and low baseline tumor size. The tumor metabolic volume by MTV and TLG at pretreatment was clarified as a significant predictor for combined chemotherapy with PD-1 blockade, but not maximal glycolytic level by SUVmax .